2022
DOI: 10.1001/jamadermatol.2021.4926
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of Biomarkers and Critical Evaluation of Biomarker Validation in Hidradenitis Suppurativa

Abstract: IMPORTANCEThe identification and validation of biomarkers in hidradenitis suppurativa (HS) has potential to improve the understanding and management of this chronic, burdensome disease.OBJECTIVE To systematically identify all known HS biomarkers, categorize them by biomarker type, and critically evaluate their validity according to established criteria.EVIDENCE REVIEW Eligibility criteria for this review (PROSPERO Registration 230830) included randomized clinical trials, uncontrolled clinical trials, cohort st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 116 publications
0
26
0
Order By: Relevance
“…Despite turning down genetic assessment, the patient's sibling discussed in case one suffered from Crohn's disease, which is associated with HS (PMC8130070). In both cases, we observed a lack of response to standard HS treatment modalities, which albeit a frequent occurrence, may be more significant in patients with underlying genetic variation and can be considered a negative predictive biomarker (9). Of note, several inactivating mutations have also been reported in genes located downstream to the MVK gene in the isoprenoid synthesis pathway.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Despite turning down genetic assessment, the patient's sibling discussed in case one suffered from Crohn's disease, which is associated with HS (PMC8130070). In both cases, we observed a lack of response to standard HS treatment modalities, which albeit a frequent occurrence, may be more significant in patients with underlying genetic variation and can be considered a negative predictive biomarker (9). Of note, several inactivating mutations have also been reported in genes located downstream to the MVK gene in the isoprenoid synthesis pathway.…”
Section: Discussionmentioning
confidence: 62%
“…Interestingly, rare autoinflammatory syndromes have HS as a key cutaneous manifestation (8). Patients with syndromic HS typically suffer from severe forms of HS with unusual skin location and signs of systemic inflammation, and resistance to conventional treatments is often reported (9). Treatment of syndromic HS is challenging and should be personalized (10).…”
Section: Introductionmentioning
confidence: 99%
“…Such endeavors require large-scale multicenter, collaborative genomic efforts ( Daxhelet et al, 2021 ; Jabbour et al, 2021 ) which will allow for endotyping ( González-Manso et al, 2020 ), deep phenotyping and, ultimately precision medicine ( Robinson, 2012 ; Delude, 2015 ) for HS patients. Genetic variables also have the propensity to act as diagnostic and predictive HS biomarkers ( Der Sarkissian et al, 2022 ). The evidence outlined in this review suggests that considering HS as a single disease may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…Clinically relevant biomarkers could be helpful. A recent systematic review critically evaluated biomarkers in HS, and showed that only one diagnostic (serum IL-2R), one monitoring (dermal Doppler vascularity), and two predictive biomarkers (epithelialized tunnels and positive family history of HS) achieved a high GRADE (grading of Recommendations, Assessment, Development, and Evaluation), but none of them had sufficient clinical validity to be recommended for routine use in the clinical setting [ 196 ].…”
Section: Discussionmentioning
confidence: 99%